Non-emergent obstetric complications and their management in primary care - Turkistani, Ohoud Adel; Alraddadi, Manar Hassan; Alsinan, Fatimah Abdullatif; Aman, Mamdouh Mohammed; Alshammari, Samar Oweid; Alqahtani, Fahad Juwayid; Alkhalifah, Bodour Saleh; Alzaki, Eman Shaker; Alharbi, Aziza Salem; Alghannam, Abdulaziz Ali; Alyami, Bandar Aedh (International Journal Of Community Medicine And Public Health, 2022)
Maternal mortality is a significant challenge faced worldwide. Reduction in maternal mortality is one of the integral goals of Millennium development goal and sustainable development goal. Obstetric complications are the leading cause of maternal mortality. Untreated non-emergent obstetric complications can also lead to severe implications and complications thus assessment, early detection and management of such complications is critical especially at primary healthcare level since it is the immediate contact. The purpose of this research is to review the available information about non-emergent obstetric complications and their management in primary care. During pregnancy, women often visit their primary care providers because of common ailments which may be caused or exacerbated during pregnancy, also may require special attention for healthy maternal and fetal outcomes. Primary care physicians should be familiar with the distinct diagnosis of obstetric complications and in case of emergency provide timely referrals. Primary care physicians by their effective intervention and management of non-emergent obstetric complications can efficiently reduce health risk of serious complications including routine screening for anaemia, pre-eclampsia and gestational diabetes to avoid significant morbidity. Primary care physicians can also reduce the burden of antenatal depression by providing psychological counselling at primary centres. Primary healthcare services have critical role in assessment and management of non-emergent obstetric complications however the available literature is quite limited and scarce in this aspect and further research can only be beneficial in highlighting its role.